REPRESENTASI FEMINISME PADA TARI SIPATMO (SEMIOTIKA PERSPEKTIF ROLAND BARTHES) - Dina Sudarmika; M. Tazul Arifin (FISIP Universitas Bung Karno, 2021)
Abstract This research discusses the feminism contained in Tari Sipatmo . The purpose of this study is to reveal the meanings of feminism contained in the Sipatmo dance. The benefits of this research, the author hopes that the reader will better understand the meaning contained in the Tari Sipatmo . The research method used to analyze the Sipatmo is to use a qualitative approach with semiotic analysis in the perspective of Roland Barthes. The time of the research took from February to July 2019. The data collection technique used documentation and video. The results of this study indicate that there are signs of feminism contained in the Tari Sipatmo . Finally, the author can conclude that the signs of feminism contained in the Sipatmo dance are the crown, earrings, scarf, soja movement, movement, ngawen, thin movement, japin movement, nindak siliwang movement, lenggang overlapping movement, and tapak dua movement.Keywords: Representation of Feminism, Semiotics,Tari Sipatmo. Abstrak Penelitian ini membahas feminisme yang terkandung dalam Tari Sipatmo. Tujuan dari penelitian ini adalah untuk mengungkapkan makna feminisme yang terkandung dalam tarian Sipatmo. Manfaat penelitian ini, penulis berharap pembaca akan lebih memahami makna yang terkandung dalam Tari Sipatmo. Metode penelitian yang digunakan untuk menganalisis Sipatmo adalah dengan menggunakan pendekatan kualitatif dengan analisis semiotik dalam perspektif Roland Barthes. Waktu penelitian berlangsung dari Februari hingga Juli 2019. Teknik pengumpulan data menggunakan dokumentasi dan video. Hasil penelitian ini menunjukkan bahwa ada tanda-tanda feminisme yang terkandung dalam Tari Sipatmo. Akhirnya, penulis dapat menyimpulkan bahwa tanda-tanda feminisme yang terkandung dalam tarian Sipatmo adalah mahkota, anting-anting, syal, gerakan soja, gerakan, ngawen, gerakan tipis, gerakan japin, gerakan nindak siliwang, gerakan lenggang tumpang tindih, dan gerakan tapak dua.Keywords: Representation of Feminism, Semiotics,Tari Sipatmo.